Editorial (Revista Lusófona de Economia e Gestão das Organizações, 2017)
The Lusophone Journal of Economicsand Organizational Management(R-LEGO) is an editorialproject of the Department ofEconomics and Management ofthe Economics and ManagementSchool [ECEO], connected to theResearch Centre of the Department(CEO - Economics and OrganizationalResearch Centre).It is aimed at students, teachers,researchers and professionalswho share interests and scientificconcerns.The ECEO has been consolidatingits position both as a trainerand research hub. In this sensewe felt the need to have a publicationthat would reflect all researchthat has been conductedin recent years.